Left lower lobe sleeve lobectomy for lung cancer using the Da Vinci surgical system. Issue 1 (December 2016) - Zhao, Yandong; Jiao, Wenjie; Ren, Xiaoyang; Zhang, Liangdong; Qiu, Tong; Fu, Bo; Wang, Lei
Abstract Background Despite the robotic surgery is widely applied, sleeve lobectomy for lung cancer using the Da Vinci surgical system is still less performed. We described a sleeve lobectomy for adenocarcinoma located at the left lower lobe using the Da Vinci surgical system. Case presentation A case of 57-year old female referred to our hospital. Computed tomography scan showed an occupation located at the left lower lobe and adenocarcinoma project from the lobe bronchus was diagnosed by bronchoscope examination. A sleeve lobectomy was performed using the Da Vinci surgical system and the postoperative recovery was uneventful. Conclusions Robotic thoracic surgery is feasible to perform sleeve lobectomy inspite of inadequate experience.